The role of oil palm biomass recycling on soil health in oil palm plantations. (October 2019) - Tarigan, R.S.; Suhardi,; Wahyuningsih, R.; Pujianto,; Wahyuningsih, P.A.; Marichal, R.; Caliman, J.P.
Abstract: Oil palm cultivation produces a massive amount of biomass (e.g., empty fruit bunches (EFB), frond and trunk) which could be recycled directly in the plantation to maintain/improve the quality of soils. The impact of this biomass recycling, i.e., EFB and frond, - in term of chemical, physical and biological characteristics, will be analyzed. The fresh application of the EFB could alternate most of the soil parameters in line with the kinetics of the decomposition of the EFB and the release of nutrients. For example, the pH of the soil after the EFB application was higher during more than 18 months compared to the initial situation. Soil exchangeable potassium increased dramatically within a few days after EFB spreading. Frond recycling, at harvesting and pruning, modifies the chemical and physical characteristics of soils whether they were applied on heaps between palms in dedicated inter-rows, or spread on harvesting paths where they could reduce run-off and erosion. The systematic distribution of fronds in inter-rows reduced rainwater run-off by more than 30%, even on 5% gentle slopes. Subsequently, soil loss through erosion was reduced by 65% depending on the slope intensity of the terrain. Consequently, the loss of nutrients was considerably reduced, resulting in higher fertilizer efficiency. Similar measurements have been done when applying fresh EFB to the soil. The impact on soil physical fertility, i.e., rainwater infiltration rate and subsequently soil humidity are improved. We have also recorded a reduction of the soil resistance to penetration, as well as an improvement of the soil aggregate stability. Several representative parameters of soil biological activity, i.e., soil fauna feeding activity using bait-lamina test system and earthworm' population showed the positive impact of EFB applications as well as frond spreading in inter-rows.